Documentary research of clinical and epidemiological aspects of lymphoma in dogs treated at the federal rural university of Rio de Janeiro - de Paiva, Felipe Noleto [UNESP]; Silva, Danielle Carlos; Cassino, Pedro Carvalho; Costa, Thiago Souza; Fernandes, Julio Israel (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2023)
Lymphomas, malignant neoplasms that originate in the lymphocytes, have a high incidence in domestic animals. This paper aimed to describe the clinical and epidemiological findings of 200 cases of canine lymphoma evaluated over nine years (2011–2019) at the Oncology Service of the Veterinary Hospital at The Federal Rural University of Rio de Janeiro. A majority of mixed-breed canines (84/200-42%) were observed, followed by the Labrador Retriever, Pitbull, and Rottweiler with similar incidence (15/200-7.5%). The average age was 7.7 years and the most affected canines were aged approximately 3 and 11 years old (146/200-73%). As for the anatomical classification, the cases classified as multicentric (131/200-65,5%) were the most common, followed by cases of the cutaneous form (44/200-22%), alimentary form (7/200 - 3.5%), mediastinal form (5/200-2.5%), and extranodal form (16/200-6,5%). Among extranodal cases were described cases of ocular involvement (5/200-2.5%), oral cavity involvement (4/200-2%), cardiac involvement (3/200-1.5%), and pulmonary involvement (1/200-0.5%). The clinical manifestation observed was related to the affected region in the different anatomical forms. More studies of this nature are needed to profile the disease presentation and contribute to clinical identification and diagnosis.
Pesquisa documental dos aspectos clínicos e epidemiológicos do linfoma em cães atendidos na Universidade Federal Rural do Rio de Janeiro
Keywords: Canine; clinical manifestation; lymphosarcoma; retrospective study